No Room for Marginalization: Recognizing the Importance of Local Knowledge For Weather Forecasting in Mbogwe District, Tanzania (Tanzania Journal for Population studies and Development, 2022)
This article documents how smallholder farmers use local knowledge on weather forecasting in Mbogwe District, Tanzania. In particular, it examines farmers’ perceptions on weather changes, sources and types of weather information used on weather forecasting, as well as the application of local knowledge on weather forecasting. The article adopted quantitative and qualitative research methodologies. Quantitative data was collected by using household questionnaires and analysed by Statistical Package for the Social Sciences (SPSS) while qualitative data was collected through in-depth interviews and Focused Group Discussions and then analysed by content analysis. Findings indicate that 81% of the respondents reported a decrease in rainfall and 68% increase in temperature, as indicators of changes in weather. It was also found that most farmers (86%) use local knowledge in weather forecasting. Furthermore, it was found that local indicators such as observation of plant and animal behaviour, meteorological bodies and astrological bodies were used by smallholder farmers in weather forecasting. In addition, the use of local knowledge was acknowledged by smallholder farmers as the most reliable and useful source of weather forecasting. Therefore, local forecast knowledge is still a practical source of weather forecasting and it should be promoted instead of being marginalized. The study recommends that collective efforts should be put in place to enhance farmers’ use of local knowledge in weather forecasting because local knowledge is site-specific and significantly applicable in local contexts. Moreover, policy and decision makers should recognize and incorporate local knowledge of weather forecasting in various policy issues that deal with climate.